A PSYCHOSOCIAL INTERVENTION FOR MENTAL HEALTH OF PEOPLE WITH HIV (PLWH): A LITERATURE REVIEW - Reineldis Gerans; Agung Waluyo (Alta Dharma Publisher, 2019)
Mental health problems such as depression and anxiety are common for people living with Human Immunodeficiency Virus (PLWH). It may have a various negative effect on psychological well-being and the quality of life for PLWH. These adverse effects are in the form of worsening diseases, decreasing the immune system, non-compliance with ARV therapy, and even causing suicide. Various psychosocial interventions were developed to improve the mental health of PLWH. But it often creates confusion and misunderstanding because it seems to overlap each other. The effectiveness of this intervention has been widely investigated, but there is still little confirmatory research on various psychosocial intervention techniques, especially for PLWH. The study aimed at describing the psychosocial interventions for the mental health of PLWH. We conducted literature searches from multiple relevant sources. The four databases we cut included PROQUEST, PubMed, Plos One, and Ebsco. Three types of psychosocial interventions consisted of symptom-oriented interventions, supportive intervention, and meditation. Based on the kind of intervention there are several psychosocial intervention techniques such as cognitive behavior therapy (CBT), stress management, interpersonal therapy (IPT), peer support, psychoeducation, meditation, relaxation, and mindfulness. There is no difference in the effectiveness of all types and intervention techniques in improving the mental health of PLWH. Psychosocial interventions proved to have a positive effect on the mental health of PLWH. Psychosocial interventions can be combined in PLHIW therapy programs with mental health problems Keywords: PLWH, psychosocial interventions, mental health problems.